INDUCING AGENTS FOR BRONCHOSCOPY A COMPARATIVE EVALUATION OF PROPANIDID AND THIOPENTONE - Gilani, Syed Mushtaq Ahmed (Journal of Ayub Medical College Abbottabad, 1990)
ABSTRACT: In this study comparison of induction characteristics of Thiopentone and Propanidid in two groups of patients (25 each) scheduled for bronchoscopy was undertaken. The results show that Propanidid maintains better cardio-respiratory stability. There is earlier recovery and shorter anaesthetic period. Propanidid was therefore, found to be safer and more useful inducing agent than Thiopentone in bronchoscopy, more so in outdoor cases.